Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1037/ocp0000081
|View full text |Cite
|
Sign up to set email alerts
|

Different types of employee well-being across time and their relationships with job crafting.

Abstract: We used and integrated the circumplex model of affect (Russell, 1980) and the conservation of resources theory (Hobfoll, 1998) to hypothesize how various types of employee well-being, which can be differentiated on theoretical grounds (i.e., work engagement, job satisfaction, burnout, and workaholism), may differently predict various job crafting behaviors (i.e., increasing structural and social resources and challenging demands, and decreasing hindering demands) and each other over time. At Time 1, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
163
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 71 publications
12
163
2
11
Order By: Relevance
“…In addition, a recent three‐wave study of Tims, Derks, and Bakker () confirmed that work engagement can also influence the extent to which employees express job crafting behaviours at work. Moreover, in another very recent longitudinal study, Hakanen, Peeters, and Schaufeli () theorised and proved on the basis of Conservation of Resources theory (Hobfoll, ) that engagement predicts all four types of job crafting. Based on the previous findings showing that engagement is related to a resource‐seeking and challenge‐seeking behaviour, we hypothesise that engagement is positively related to seeking challenges (Hypothesis 1a), seeking structural resources (Hypothesis 1b), and seeking social resources (Hypothesis 1c).…”
Section: Work Engagement Workaholism and Job Craftingmentioning
confidence: 99%
“…In addition, a recent three‐wave study of Tims, Derks, and Bakker () confirmed that work engagement can also influence the extent to which employees express job crafting behaviours at work. Moreover, in another very recent longitudinal study, Hakanen, Peeters, and Schaufeli () theorised and proved on the basis of Conservation of Resources theory (Hobfoll, ) that engagement predicts all four types of job crafting. Based on the previous findings showing that engagement is related to a resource‐seeking and challenge‐seeking behaviour, we hypothesise that engagement is positively related to seeking challenges (Hypothesis 1a), seeking structural resources (Hypothesis 1b), and seeking social resources (Hypothesis 1c).…”
Section: Work Engagement Workaholism and Job Craftingmentioning
confidence: 99%
“…Similarly, Moon, Youn, Hur, and Kim () found that employees' spirituality at work, which enables employees to assign meaning to their work experiences, was positively related to approach crafting through increased intrinsic work motivation. For energized to motivation, several empirical studies have found positive relationships between work engagement, an activated positive affect, and approach crafting after 1 month (Tims, Bakker, & Derks, ), 3 months (Lu et al, ; Zeijen, Peeters, & Hakanen, ), 3 years (Harju, Hakanen, & Schaufeli, ), and 4 years (Hakanen, Peeters, & Schaufeli, ). Similar to work engagement, workaholism involves feelings of absorption in one's work and is positively related to approach crafting, although the motivation of workaholism is compulsive rather than intrinsic (Hakanen et al, ; Zeijen et al, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…For energized to motivation, several empirical studies have found positive relationships between work engagement, an activated positive affect, and approach crafting after 1 month (Tims, Bakker, & Derks, ), 3 months (Lu et al, ; Zeijen, Peeters, & Hakanen, ), 3 years (Harju, Hakanen, & Schaufeli, ), and 4 years (Hakanen, Peeters, & Schaufeli, ). Similar to work engagement, workaholism involves feelings of absorption in one's work and is positively related to approach crafting, although the motivation of workaholism is compulsive rather than intrinsic (Hakanen et al, ; Zeijen et al, ). Furthermore, drawing on self‐regulation theory, Zeijen et al () found that work engagement is positively related to approach crafting through self‐observation and self‐goal setting, while workaholism only through self‐goal setting.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
See 2 more Smart Citations